Prevenção da infecção por Clostriduim difficile em hamsters utilizando uma estirpe não toxigênica - Carlos Augusto de Oliveira Junior (2015)
The objectives of this study were to characterize five strains of non-toxigenic Clostridium difficile (NTCD), to assess the temporal viability of freeze-dried spores and prevent C. difficile infection (CDI) in hamsters using one NTCD strain. The tests performed were PCR and ELISA to confirm the toxigenic profile, in vitro spore production and evaluation of antimicrobial resistance profile. One strain was selected and lyophilized in several aliquots, which were kept at 4 and 20°C and subjected to three spore count methods monthly. A total of 107 spores of NTCD strain was administered to hamsters previously treated with clindamycin. The challenge with 108 spores from a toxigenic strain of C. difficile was performed 12 and 48 hours after administration of NTCD strain and the animals were observed for 28 days. Strains were confirmed as non-toxigenic, were resistant to clindamycin and lincomycin and presented resistance genes to bacitracins and tetracyclines. The production of spores in vitro ranged from 6.17 x 104 to 4.79 x 106 spore/ml. Strains stored at 20°C maintained slightly higher counts over time, with estimated shelf life of 23 months. NTCD strain was able to prevent ICD in all animals that received it and remaining in the intestine until the last experiment day.